PERANCANGAN SISTEM INFORMASI INSTALASI TELEPON BERBASIS WEB STUDI KASUS PADA TELKOM TEMBILAHAN - Hendri Saputra (Sistemasi: Jurnal Sistem Informasi, 2014)
Development of information get significant effect on the human mind and habits. The quality and service is need for growing fast becoming the hopes and desires of every human being. It became a thought and analysis that should be applied in every plan and policy to be taken especially companies that deal directly with consumers in all operation. That's because Telkom Tembilahan wants to develop the technology advances, in order to facilitate the registration of new people to do the installation Phone. Telkom Tembilahan has always put the needs and interests the comfortable for the people on Tembilahan. The service of Availability is fast, accurate and thorough in addition will assist in the process of customer service, will also be very helpful in improving managerial company and help the company to determine the next steps to be taken as a company policy. At this time PT. Telkom as the provider of online installation in operation for processing such data, especially with regard to new customers, preparing reports customer data entry has been done is by using a computerized program media web applications, but the operation is still considered to be slow, and it’s can to be a waste of time. The research has resulted in applications for website design for information registration telephone instalation implementation on telkom tembilahan. Application of the stretcher has been realized and can operate as a system requirement. In general, the new system has succeeded in optimizing the computer system in the process of registration so that it can manage the data well, to produce an effective and efficient information.